Tingkat Kepuasan Mahasiswa Terhadap Kinerja Dosen Fakultas Psikologi Dan Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta - Artopo, Vicky Ertanto Arey; , Ahmad Mardalis, SE.,MBA (2016)
This study aims to determine the level of satisfaction on the performance of students and faculty lecturer of Psychology faculty of Economics and Business, University of Muhammadiyah Surakarta, in addition to knowing the psychology department faculty performance and faculty FEB. The analysis tool used is multiple linear regression, to retrieve data using methods gave questionnaires to respondents Psychology faculty students and faculty of Economics and Business, University of Muhammadiyah Surakarta.Dari results of the analysis of each variable can be seen that the level of student satisfaction is greater than the faculty of Psychology Faculty of Economics and Business Universitas Muhammadiyah Surakarta. And the results of the research shows that the Creative Class variable factor, Factor and Factor Evaluation Strategy Class Class are able to explain the level of student satisfaction on the performance of Surakarta Muhammadiyah University lecturer at the Faculty of Psychology at 54.6% and the faculty of Economics and Business amounted to 52.4%.